Diagnostic Value of Dipstick Test (Leukocyte Esterase and Nitrite) in Diagnosis of Urinary Tract Infection - Huda, Nasreen; Nabonee, Modina Ansary; Yusuf, Md Abdullah; Hossain, Marufa; Sabiha, Kazi (Bangladesh Journal of Medical Microbiology, 2023)
Background: The accurate UTI diagnosis is crucial in the laboratory. Objective: The objective was to assess the sensitivity and specificity of the nitrite test, leukocyte esterase, both nitrite and leukocyte esterase, and urine microscopy in UTI diagnosis. Methodology: This was a cross-sectional study in which 100 adult patients, who were suspected to have UTI and did not receive antibiotics for at least 1 week, were included in this study performed in Shahabuddin Medical College and Hospital, Gulshan-2, Dhaka. Urine samples were collected and sent to laboratory for urine analysis and urine culture. Nitrite and leukocyte esterase dipsticks tests were done as well. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were measured for nitrite, leukocyte esterase, both nitrite and leukocyte esterase. Results: According to the results of the urine dipstick test, microscopy, and urine culture, nitrite was positive in 17.0% of the cases, leukocyte esterase was positive in 53.0% of the cases, both nitrite and leukocyte esterase were positive in 17.0% of the cases, urine microscopy was positive in 71.0% of the cases, and urine culture was positive in 41.0% of the cases. In the detection of urinary tract infections, the sensitivity, specificity, PPV, and NPV of leukocyte esterase were 87.8%, 71.2%, 67.9%, and 89.4% respectively, using urine culture as the gold standard test. Based on urine culture as gold standard test, the sensitivity, specificity, PPV, and NPV of both nitrite and leukocyte esterase were 34.1%, 94.9%, 82.4%, and 67.5% respectively, in detecting urinary tract infections. Conclusions: Efficacy of leukocyte esterase was found better in detecting UTI comparing nitrite test. Escherichia coli is the most common isolated organism. Bangladesh Journal of Medical Microbiology, July 2023;17(2):55-59 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />